An Integrated Approach to the Treatment of Pulmonary Embolism: Current State of the Problem - Yaroslav V. Khrebtiy (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. Treatment of venous thromboembolism remains perhaps the most challenging problem of modern phlebology. The aim of our study was to analyze current data and guidelines on the use of surgical and minimally invasive approaches in the treatment of pulmonary embolism (PE) and to compare these with our own results.Materials and methods. The results of treatment of 168 patients with PE, who underwent inpatient treatment at the clinic from 2009 to 2021, were analyzed. Among them, 162 (96%) patients had deep vein thrombosis, in 6 patients the cause of PE could not be identified. Recurrent PE was observed in 2 patients. PE with a high risk of death was observed in 51 (30.3%) patients, with a medium and low risk of death in 117 patients (69.6%).Systemic thrombolysis was performed in 44 (26%) cases. In 5 (2.9%) cases, vena cava filters were implanted. One (0.6%) patient underwent aspiration thrombectomy of the pulmonary artery using an Aspirex catheter. Two (1.1%) patients underwent pulmonary artery thrombectomy using an artificial circulation device.Results. Significant improvement in patients treated with thrombolytic therapy was observed in 40 (92.8%) cases. After surgical treatment of PE, significant improvement was observed in 100% of cases, 2 patients after PE showed complete de-obstruction of the pulmonary artery. No hemorrhagic complications were observed during the study period. No fatalities were reported. No recurrent PE was observed during the study period.Conclusions. The choice of treatment for PE is determined by the degree of the impact on the pulmonary tract, the stability of the patient’s condition, indicators of dysfunction of the right heart, the period from the onset of the disease, the risk of death.The use of aspiration thrombectomy using an Aspirex catheter (Straub, USA) and pulmonary artery embolectomy in the absence of thrombolytic therapy allows to obtain satisfactory results in patients with PE.